Analysis of the Judge's Considerations Rejecting Applications for the Court Order of Guardianship And Permission to Sell Land Rights Owned by Minors And the Legal Implications Regarding Deeds of Sale And Purchase by PPAT (Study of the Court Order of the Sangatta District Court Number: 13/Pdt.P/2023/PN.Sgt) - Arini Prasetiyowati (Journal of Law, Politic and Humanities, 2024)
The purpose of this research is to find out the judge’s considerations in rejecting the application for guardianship and permission to sell land rights belonging to a minor child by his biological mother in the Court Order of the Sangatta District Court Number 13/Pdt.P/2023/PN.Sgt. The methodology is doctrinal research, by relating the main research problem with legal theory, legislation, and court precedence relating to guardianship of minors and permission to sell. This research was analyzed using an empirical juridical approach, by analyzing the legal material and then examining the results of the analysis with interviews. The researcher attemped to providing a perspective and solution to the problem raised. The results showed that the judge rejected the application with the consideration that the living parent automatically exercises parental authority and is free to take legal action on behalf of their children both before and outside the court without applying a guardianship application. The impact of the decision can be interpreted that the applicant can carry out the legal actions, including signing a deed of sale and purchase of the inherited land without a guardianship court order or permission to sell from the court. This creates legal uncertainty and confusion in the process of making a deed of sell and purchase by the Land Titles Registrar (PPAT). A sale and purchase deed made without a guardianship court order and permission from the court or a deed made on the basis of a judge’s consideration as in the court order decision, the registration process would be declined by the Land Registry Office. For similar cases that may occur in the future, it will open up the possibility of parents arbitrarily exercising parental authority because there is no supervision by judge in the form of Court Order of Guardianship and permission to sell Land Rights belonging to minors